Therapeutic Communication As A Solution To Overcome Adolescent Problems - Tutik Astuti; Listia Dwi Febriati; Zahrah Zakiyah; Ester ratnaningsih (International Assulta of Research and Engagement (IARE), 2023)
This community service aimed to enhance parents' knowledge and therapeutic communication skills regarding adolescent issues in Padukuhan Duku, Jambidan Village. Conducted on August 1, 2023, the activity involved 17 parents, focusing on adolescent problems and solutions through counseling. Findings revealed a positive shift in knowledge levels, with a significant increase in the "Good" category from 70.59% to 82.35%. The paired sample T-test indicated a significant difference (p=0.024) between pre-test and post-test knowledge levels. The majority of participants were over 36 years old, had secondary education, and were not working. This community service contributes to the understanding of the critical role parents play in shaping adolescents' development, emphasizing the importance of effective communication. The success of the intervention suggests its potential applicability to similar community initiatives. In conclusion, the activity effectively increased parents' knowledge and therapeutic communication skills, highlighting the significance of continuous parent-adolescent communication for reproductive health knowledge and overall well-being.